2020
DOI: 10.1088/1361-648x/abd0c2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and topological properties of group-10 transition metal dichalcogenides

Abstract: The group 10 transition metal dichalcogenides (TMDs) (MX 2: M = Ni, Pd, Pt; X = S, Se, Te) have attracted much attention in the last few decades because of observation of exotic phases and phenomena such as superconductivity (SC), topological surface states (TSSs), type II Dirac fermions, helical spin texture, Rashba effect, 3D Dirac plasmons, metal–insulator transitions, charge density waves (CDW) etc. In this review, we cover the experimental and theoretical progress on the physical phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 165 publications
0
12
0
Order By: Relevance
“…[21][22][23][24][25] Furthermore, group 10 noble metal dichalcogenides (NMDCs) have attracted increasing attention recently. [26][27][28][29][30] NMDCs not only possess anisotropic structures, low-energy differences between different crystalline phases and controllable phase transitions compared to conventional TMDCs, but also exhibit promising application potential in field-effect transistors, photodetectors, sensors, photocatalysts and photovoltaic cells. [31][32][33][34][35][36][37] Particularly, the bulk phases of diselenides or disulphides of palladium (PdX 2 , X = S, and Se) crystallize in a peculiar puckered pentagonal structure (2O type), instead of the common 1T, 2H or 3R structure of TMDCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24][25] Furthermore, group 10 noble metal dichalcogenides (NMDCs) have attracted increasing attention recently. [26][27][28][29][30] NMDCs not only possess anisotropic structures, low-energy differences between different crystalline phases and controllable phase transitions compared to conventional TMDCs, but also exhibit promising application potential in field-effect transistors, photodetectors, sensors, photocatalysts and photovoltaic cells. [31][32][33][34][35][36][37] Particularly, the bulk phases of diselenides or disulphides of palladium (PdX 2 , X = S, and Se) crystallize in a peculiar puckered pentagonal structure (2O type), instead of the common 1T, 2H or 3R structure of TMDCs.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47][48][49][50] Owing to the low-symmetry pentagonal layer structure, PdX 2 materials show intriguing properties including layer-related band gaps, bipolar charge transport with high carrier mobility, excellent thermoelectric performances, and pressure/strain modulated superconducting and ferroelastic phenomena. 23,[26][27][28][29][30][51][52][53][54][55][56] Furthermore, the bulk phases of PdX 2 hold the Pbca space group and the D 2h (mmm) point group, while the symmetries of few-layer PdSe 2 differ from those of the bulk phase. 57 The evenlayer PdSe 2 belongs to the Pca2 1 space group and C 2v (mm2) point group without inversion symmetry, whereas the odd-layer PdSe 2 belongs to the P2 1 /c space group and C 2h (2/m) point group with inversion symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive theoretical and experimental investigations have been reported showing that group-10 transition-metal dichalcogenides (TMDs), such as PtSe 2 , PtTe 2 , and PdTe 2 , hold type-II Dirac Fermions . Access to the Dirac Fermions in these TMDs, however, is quite limited because the Dirac points are located far away from the E F . Therefore, the physical signature of relativistic particles is obscure because the electronic properties are mainly governed by the electrons at the E F . Several efforts have been made to resolve this issue in type-II Dirac materials.…”
mentioning
confidence: 99%
“…Fei et al showed that the E F can be tuned close to the bulk Dirac point (BDP) in IrTe 2 by doping with Pt . On the other hand, it was reported that NiTe 2 , another group-10 TMD, holds the BDP slightly above the E F by 70–100 meV, implying an ideal type-II Dirac system. ,, Then, the additional tunability of E F in NiTe 2 will greatly enhance the possibility of applications utilizing type-II Dirac Fermions.…”
mentioning
confidence: 99%